2015
DOI: 10.1093/nutrit/nuv024
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between living alone and food and nutrient intake

Abstract: The increase in the number of individuals living alone has implications for nutrition and health outcomes. The aim of this review was to investigate whether there is a difference in food and nutrient intake between adults living alone and those living with others. Eight electronic databases were searched, using terms related to living alone, nutrition, food, and socioeconomic factors. Forty-one papers met the inclusion criteria, and data of interest were extracted. Results varied but suggested that, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 74 publications
6
77
2
Order By: Relevance
“…28 Economic factors could explain the lower consumption of certain foods, such as fish, fruits, and vegetables, which require more regular consumption, as frequent purchase can also be more expensive. 29 Similar to the present study, Hunter et al 30 compared living alone with living with others and showed that living alone was associated with lower consumption of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…28 Economic factors could explain the lower consumption of certain foods, such as fish, fruits, and vegetables, which require more regular consumption, as frequent purchase can also be more expensive. 29 Similar to the present study, Hunter et al 30 compared living alone with living with others and showed that living alone was associated with lower consumption of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 83%
“…Demographic data have shown that the groups living alone most likely to be affected by economic factors are men and senior women who have lower incomes than persons of the same age living with others . Economic factors could explain the lower consumption of certain foods, such as fish, fruits, and vegetables, which require more regular consumption, as frequent purchase can also be more expensive . Similar to the present study, Hunter et al compared living alone with living with others and showed that living alone was associated with lower consumption of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 75%
“…Among subjects with elevated depressive symptoms, alexithymia associated less often with a prudent dietary pattern and more frequently with an unhealthy Western dietary pattern. All these associations remained unaltered after multiple adjustments for potential confounders, such as age (Zang, Yu, Zhu et al ., ), gender (Elfhag & Lundh, ), level of education (Zang et al ., ), marital status (Hanna & Collins, ), a poor financial status (Zang et al ., ), alcohol use (Robino et al ., ; Zang et al ., ) and daily smoking (Zang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have looked into the role of family structure on dietary intake [57], few have evaluated the effect of number of siblings on adolescent dietary patterns [8–10]. One of these studies found that individuals with no siblings had a higher daily intakes of nutrients (except carbohydrate and added sugars) compared to individuals with siblings, suggesting that only-children may have a better diet quality [9].…”
Section: Introductionmentioning
confidence: 99%